Trade-off analysis of agri-food systems for sustainable research and development - Antle, John M.; Valdivia, Roberto O. (Oxford University Press, 2021)
Tradeoff Analysis (TOA) is an approach to positive analysis that combines foresight analysis and simulation modeling tools from the relevant disciplines, including economics, in a participatory process designed to formulate and evaluate forward-looking, strategic decisions under high levels of uncertainty in complex systems. We motivate TOA with a prototype framework for the design and evaluation of public-good agricultural research for sustainable development. We discuss the advantages of TOA over conventional economic analysis-Benefit-Cost Analysis-for the design and evaluation of sustainable development pathways. The remainder of the paper describes the currently available modeling tools and their strengths and limitations for use in TOA, and illustrates recent applications with cross-scale case studies. We conclude with a discussion of the opportunities and challenges for the use of foresight analysis and TOA in research priority setting and management at global and project levels, using the case of the CGIAR to illustrate.